Structure and rheology of polyethylene/imidazolium‐based montmorillonite nanocomposites. Issue 2 (27th April 2012) - Médéric, P.; Le Pluart, L.; Aubry, T.; Madec, P.‐J.
Abstract In this study, nanocomposites based on linear low density polyethylene (PE) and organomodified montmorillonites (MMTs) have been processed without adding any other polar compatibilizer such as maleic anhydride grafted PE. We evidence the beneficial effect on the state of dispersion of an imidazolium‐based MMT compared to traditional commercial organoclays, one of which being its alkylammonium equivalent. Transmission electron microscopy observations and melt rheology are used to characterize the state of dispersion of clay in the polymer matrix. Thinner primary particles and lower interparticle distances are obtained with the imidazolium‐based MMT. This result is attributed to a higher initial gallery spacing which favors delamination phenomena. As a consequence, the dispersion state of this organoclay is much more sensitive to changes in the mixing shear rate, contrarily to the commercial ones. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013